Clostridium difficile Infection in Liver Transplant Recipients: A Retrospective Study of Rates, Risk Factors and Outcomes. Issue 8 (5th June 2014) - Mittal, C.; Hassan, S.; Arshad, S.; Jeepalyam, S.; Bruni, S.; Miceli, M.; Jacobsen, G.; Abouljoud, M.; Bajjoka, I.; Ramesh, M.; Alangaden, G.
<x xml:space="preserve">Abstract</x> Clostridium difficile infection (CDI) occurs in 3–7% of liver transplant recipients (LTR). However, few data exist on the recent epidemiology, predictors and outcomes of CDI in LTR. A cohort study was performed including LTR from 2000 to 2010 at a tertiary care hospital in Detroit. CDI was defined as diarrhea with a stool C. difficile positive test. Data analyzed included demographics, comorbidities, length of stay (LOS), severity of CDI, rates of recurrence (<12 weeks), relapse (<4 weeks) and overall mortality. Predictors of CDI were calculated using Cox proportional hazard model; 970 LTR were followed for years. Overall prevalence of CDI was 18.9%. Incidence of CDI within 1 year of transplant was 12.4%. Severe CDI occurred in 29.1%. CDI recurrence and relapse rates were 16.9% and 9.7%, respectively. Independent predictors of CDI were year of transplant (hazard ratio [HR] 1.137, 95% confidence interval [CI] 1.06–1.22; p < 0.001), white race (105/162 whites, HR 1.47, 95% CI 1.03–2.1; p = 0.035), Model for End‐Stage Liver Disease score (HR 1.03, 95% CI 1.01–1.045, p = 0.003) and LOS (HR 1.01, 95% CI 1.005–1.02, p < 0.001). Significant mortality was observed among LTR with CDI compared to those without CDI (p = 0.003). We concluded that CDI is common among LTR and is associated with higher mortality.